Pasture recovery using Stylosanthes cv. Campo Grande: effect on soil quality - Bisi, Beatriz Santos [UNESP]; Batista Bonini, Carolina dos Santos [UNESP]; Neto, Alfredo Bonini [UNESP]; Heinrichs, Reges [UNESP]; Meirelles, Guilherme Constantino [UNESP]; Oliverio, Gabriela Lozano [UNESP]; Mateus, Gustavo Pavan; Silveira do Nascimento, Cleiton Alexandre [UNESP] (Univ Federal Rural Pernambuco, 2019)
The objective of this study was to study the physical attributes and the organic matter of a Red-Yellow Oxisol cultivated with Urochloa decumbens pasture in recovery with different introducing ways of Stylosanthes cv. Campo Grande. The experiment was conducted at the Agency for Agribusiness Technology of Sao Paulo (APTA), in the municipality of Andradina/SP, between October 2016 and September 2017. The experimental design was the randomized complete block design with four replicates and the treatments were composed of six strategies (partial desiccation, total desiccation, scarification, rome harrowing and plowing + harrowing.) in the no-tillage legume in the pasture, in addition to the control. Stability of aggregates, flocculation, soil porosity, organic matter and soil texture were evaluated in three layers: 0-0.10; 0.10-0.20 and 0.20-0.40 m. Soil organic matter content was higher in the topsoil layers (from 15.75 to 17.75 mg dm(-3)) and decreased with depth (from 10.50 to 11.50 mg dm(-3)). The indicated macroporosity was below the value considered ideal for the plants development. Studied treatments did not influence the organic matter content, porosity and soil density. Soil quality was influenced up to 0.20 m with the introduction of stylosanthes, regardless of the adopted management.
Keywords: degraded area; organic matter; physical attributes